2006
DOI: 10.1177/0363546505281808
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hip Muscle Function in the Treatment of Patellofemoral Pain Syndrome

Abstract: Improvements in hip flexion strength combined with increased iliotibial band and iliopsoas flexibility were associated with excellent results in patients with patellofemoral pain syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
6
18

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(162 citation statements)
references
References 32 publications
5
133
6
18
Order By: Relevance
“…7,[12][13][14][15]22,39,40,42 However, few of these studies evaluated the efficacy of isolated quadriceps strengthening. Many published rehabilitation protocols target functional exercises in a weight-bearing position, which requires a contribution of both hip and quadriceps musculature.…”
Section: T T Conclusionmentioning
confidence: 99%
“…7,[12][13][14][15]22,39,40,42 However, few of these studies evaluated the efficacy of isolated quadriceps strengthening. Many published rehabilitation protocols target functional exercises in a weight-bearing position, which requires a contribution of both hip and quadriceps musculature.…”
Section: T T Conclusionmentioning
confidence: 99%
“…These changes in quadriceps activation have been associated with symptomatic relief and successful outcomes on patients with PFPS. 29 Several investigators have suggested that proximal hip muscle weakness, particularly of the hip abductors and external rotators, may be associated with patellofemoral pain, 2,30 and Tyler et al 31 reported that improvements in hip flexor strength and flexibility were associated with symptomatic improvement in patients with PFPS. 31 The implication of the findings of these studies is that addressing MT combined with physical therapy on the full kinetic chain may be an important element in the successful rehabilitation of patients with PFPS.…”
Section: Discussionmentioning
confidence: 99%
“…This factor is justified in that adequate dynamic control of the pelvis helps patients improve the mechanics of the patellofemoral joint (15).…”
Section: Discussionmentioning
confidence: 99%
“…There is no standard recommended treatment, although it is believed that conservative non-surgical approaches produce good results, with a resolution rate of up to 87% (5). Conventional treatment generally includes physiotherapy (14), strengthening the quadriceps, using a knee brace and taping, as well as soft tissue mobilization and stretching (15,16). In this respect, muscle strengthening aims to combat neuromuscular deficits, which include the quadriceps, vastus medialis oblique muscle, proximal muscle strength deficits, soft tissue tightness or abnormal knee alignment (17).…”
Section: Introductionmentioning
confidence: 99%